“The Golden Age of the Russian Old Believers and Sectarianism”: reform of the legal status of Old Believers and sectarians 1905-1906 through the prism of law enforcement - A. S. Tumanova; A. A. Safonov (Правоприменение, 2023)
The article contains an analysis of the legal situation of sectarians and Old Believers of various consents after the publication of decrees on April 17, 1905 "On strengthening the principles of religious tolerance" and on October 17, 1906 "On the procedure for the formation and action of Old Believer and sectarian communities." The study is based on the materials of the Russian socio-political and Old Believer press, documents of private origin (diary entries of public and state figures), etc.The focus of the authors' attention is government decrees and circulars, as well as materials of lawsuits against Old Believers and sectarians. The authors recreate the law enforcement context of the implementation of the confessional reform of 1905–1906 and its impact on the legal life of representatives of Old Believer consents and sectarians, in particular, representatives of the so-called "Izuver" sects. Using the possibilities of formal-legal, comparative-legal and especially historical-biographical methods of historical-legal research, involving the analysis of current legislation by contemporaries, the authors come to the conclusion that the practice of applying new legislation contained numerous problem places. There were bureaucratic methods of reform, and dubious in some cases expert opinions of missionaries at trials, and a lack of understanding of the differences between Old Believers and sectarians, and other factors that make up the so-called "executor effect," which hindered the implementation of religious reform. The main drawback of law enforcement practice was seen by religious scholars in maintaining the principle of administrative guardianship of religious societies, which reflected the inconsistency of state policy in this matter.